Inertial behavior of gravity-type quay wall: A case study using dynamic centrifuge test. Issue 155 (April 2022) - Kim, Yeon Sam; Lee, Moon-Gyo; Cho, Gye-Chun; Ko, Kil-Wan
Abstract: Quay walls have been extensively investigated since the 1995 Kobe earthquake, with most studies focusing on the revision of design codes and evaluation of seismic active earth pressure. To ensure the quay wall's safety during a strong earthquake, many studies evaluated the interaction between the wall and the backfill soil. Although several studies have reported that the inertial behavior of the quay wall can cause the failure due to its inertia force, the test case describing the dynamic inertial behavior of the quay wall and its failure development has not been introduced enough. In this study, a centrifuge test was introduced to describe failure mechanism of a gravity-type quay wall manifested by its large inertia. The frequency characteristics of the quay wall was discussed using analytical calculations and the transfer functions from the test results. It showed that the analytical calculations well predicted the natural frequencies of the wall under a weak dynamic loading. Under a strong shaking, the natural frequencies of the wall were significantly different from that of the backfill and it implied that the phase difference occurrence between the wall and the backfill due to the wall's inertial behavior. The test results showed that soil liquefaction was induced during the strong dynamic loading only at the backfill soil, followed by vertical settlement of ground due to void redistribution. Consequently, horizontal sliding failure due to the inertial motion of the quay wall was also noted. Highlights: A centrifuge test case for evaluating failure mechanism of a gravity-type quay wall regarding its inertial behavior was introduced. Frequency characteristics of quay wall under weak and strong earthquakes were evaluated analytically and experimentally. Relationship between quay wall movement, excess pore water pressure response, and backfill ground settlement was discussed. Sliding failure of quay wall was governed by its inertial motion than liquefaction occurrence or excess pore pressure development at the backfill.